PENGARUH PENERAPAN STRATEGI TIPE DREADLINES TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS VII SMPN 1 SIJUNJUNG - Akmal, Arijal; Mukhni, Mukhni; Husna, Husna (STKIP PGRI Sumbar, 2013)
This research was done due to the grade-VII studentsâ mathematic communication at SMPN 1 Sijunjung which was low. The research aimed at finding out whether the grade-XI studentsâ understanding of mathematic communication by implementing the dreadlines strategy was better than by implementing the conventional strategy. The design of the research was experimental research. The population was all grade-VII students at SMPN 1 Sijunjung of 2012-2013. The sample was taken randomly. Grade VII 1 was the experiment group while grade VII 2 was the control group. The instruments of the research were post-test and communication indicators. The test used was essay test with its reliability r11 = 0.93 the data were analyzed by using the one-way t-test using MINITAB. Based on the result of hypothesis analysis, it was obtained the P-Value = 0,001 which meant lower than Î± = 0,05 so that the hypothesis of the research was accepted. Therefore, it was concluded that studentsâ mathematic communication using the dreadlines strategy was better than studentsâ mathematic communication using the conventional learning.